Making Drosophila lineage-restricted drivers via patterned recombination in neuroblasts. - Awasaki, T.; Kao, C.F.; Lee, Y.J.; Yang, C.P.; Huang, Y.; Pfeiffer, B.D.; Luan, H.; Jing, X.; Huang, Y.F.; He, Y.; Schroeder, M.D.; Kuzin, A.; et al. (Nature Neuroscience, 2014)
The Drosophila cerebrum originates from about 100 neuroblasts per hemisphere, with each neuroblast producing a characteristic set of neurons. Neurons from a neuroblast are often so diverse that many neuron types remain unexplored. We developed new genetic tools that target neuroblasts and their diverse descendants, increasing our ability to study fly brain structure and development. Common enhancer-based drivers label neurons on the basis of terminal identities rather than origins, which provides limited labeling in the heterogeneous neuronal lineages. We successfully converted conventional drivers that are temporarily expressed in neuroblasts, into drivers expressed in all subsequent neuroblast progeny. One technique involves immortalizing GAL4 expression in neuroblasts and their descendants. Another depends on loss of the GAL4 repressor, GAL80, from neuroblasts during early neurogenesis. Furthermore, we expanded the diversity of MARCM-based reagents and established another site-specific mitotic recombination system. Our transgenic tools can be combined to map individual neurons in specific lineages of various genotypes.